Upaya Pengembangan Karir Guru Melalui Peningkatan Kualifikasi Akademik dan Profesionalisme (Studi pada Guru-Guru SMP di Kabupaten Bengkalis) - Zulkifli Hasan (Akademika: Jurnal Keagamaan dan Pendidikan, 2017)
Career development in the field of faith development and values, skills and talents, interests, personality characteristics, and knowledge of the world of work as far as life.Based on this understanding, career development covers not only the working age range of a person, much more, throughout a person’s lifetime. This career development includes the development of beliefs and a person concerning the world of work, the people I have to believe in ‘guts’ of what he does (work) for his life and apply the things that drive his life’s progress, for example: craft, tenacity , honesty, unyielding and thrifty. Adjustment of interest and talent with the work that he wrestle is also a career development effort that is a little more quality and quantity of a person. A person’s academic qualifications are very influential in developing his or her next career. so in this case able to improve professionalism as a teacher.